Pendidikan Karakter Dalam Surat Al-Ahzab Ayat 21 Perspektif Tafsir Al-Misbah Karya Muhammad Quraish Shihab - Siti Fatimah; Suparno (Jurnal Pendidikan Agama Islam Miazhar, 2021)
Character education is a very important national foundation and needs to be instilled in children from an early age. Therefore, the impact of globalization that is happening at this time has brought the Indonesian people to forget the character of the nation. Talking about education is never ending. Various educational problems have emerged along with the times. Likewise, the solution is that there are more and more opinions, opinions, journals, articles and even special research on education, both theoretical and empirical studies. The problems that can be formulated are 1. How are the values ​​of character education in Surah al-Ahzab verse 21 from the perspective of Tafsir al-Mishbah by Muhammad Quraish Shihab?, 2. How is the contribution of the concept of character education values ​​in Surah al-Ahzab 21 from the perspective of Tafsir al -Mishbah according to Muhammad Quraish Shihab on the development of Islamic religious education? The objectives to be achieved are 1. To describe the values ​​of character education contained in the letter al-Ahzab verse 21 from the perspective of the interpretation of al-Misbah by Muhammad Quraish Shihab. 2. To describe the contribution of the concept of character education values ​​contained in the letter al-Ahzab verse 21 from the perspective of the interpretation of al-Mishbah by Muhammad Quraish Shihab to the development of Islamic religious education. In this section the author will briefly explain about Tafsir al-Mishbah, both in terms of choosing the name, source, method, style, and systematic interpretation of Tafsir al-Misbah. the source of interpretation here is the things or materials used to explain the meaning and content of the verse or according to M. Yunan Yusuf, that is the way a commentator gives his interpretation, whether to interpret the Koran by using the Koran with al-Hadith, the Koran with the history of the Companions, the story of Israel, or interpreting the Koran. 'an with filkiran (ra'y). Character education contained in Q.S. Al-Ahzab verse 21 includes: siddiq is a true reality that is reflected in words, deeds or actions, and the circumstances that exist in the Apostle, trust is a belief that must be carried out in realizing something that is done with commitment, competence, hard work , and consistent, fhatanah is an intelligence, skill, or mastery of a particular field that includes intellectual, emotional, social and spiritual intelligence, and tabligh is an effort to realize a certain message or mission carried out with a certain approach or method. These four characters by some scholars mention the character inherent in the Apostle who must be imitated by mankind.